Membangun Strategi Pemasaran dalam Meningkatkan Daya Saing Bisnis Pasca Pandemi Covid-19 - Abdurrahman Abdurrahman; Nila Rahayu; Yeldi Dwi Genadi; I.G.A. Arista Pradnyani (Universitas Bumigora, 2022)
This study entitled Establishing Marketing Strategy to Improve Competitive Advantage of Business Pasca Pandemic Covid-19. The aim is to determine the effect of marketing strategy in increasing business competitiveness after the Covid-19 pandemic. The objects of this research are business actors, in this case students at the Faculty of Economics and Business who own businesses and have been running for at least one year. The sampling technique used in this study is Quota Sampling, where the number of samples has been determined in advance, in this case the respondents are business actors from students who are members of the Student Preneuship Program at the Faculty of Economics and Business, University of Mataram. Analysis and testing of hypotheses used the Statistical Package for the Social Sciences (SPSS) with research instruments using questionnaires which were distributed online with the help of Google forms. The analysis carried out in this research is multiple linear regression analysis, while the testing stages are validity test, reliability test, multiple regression analysis, hypothesis testing through F test and t test, with product moment correlation coefficient. From the regression analysis, the equation is obtained Y = 1.013 + 0.471X1 + 0.251X1 + 0.382X3 + 0.211X4. Hypothesis testing using the F test shows that the four independent variables studied are proven to simultaneously influence purchasing decisions, where the value of F count> F table (7.514 > 2.58).